Information System Agility And Covid-19: An Exploratory Model to Minimze Pandmeics Effects On Small and Medium Enrprises (Global Journal of Management and Business Research, 2024)
Over the past few years, many small and medium enterprises (SMEs) have adopted agile information systems (IS) as they try to adapt to the uncertainties of the COVID-19 pandemic that not only resulted in many deaths but also disrupted the markets for the products and services of most SMEs. The aim of this research is to propose an exploratory model to explain the relationship between consumers, SMEs, and agile information systems and how they influence decision-making and financial decisions during and after the COVID-19 pandemic. The researchers employed qualitative methods as the research strategy for this study and supplemented their findings with quantitative approaches applied to a brief case study. The independent variables intelligence, flexibility, awareness, and competencies have a significant effect on the dependent variable information system agility. R 2 for the independent variables is (0), and R 2 for the dependent variable is 0.66; consequently, the hypotheses of the research are statistically accepted. An exploratory model was created based on the theoretical background and statistical analysis of the obtained data. The proposed model includes operative functionalities, a build and design section, and an implementation section, which provide consumers with the best user experience without contacting the SMEs administrators.
Keywords: agility; COVID-19; information system; dynamic capabilities